menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Solve the following equation. (3y - 2)/3 + (2y + 3)/2 = y + 7/6
asked
Feb 21, 2022
52.2k
views
1
vote
Solve the following equation.
(3y - 2)/3 + (2y + 3)/2 = y + 7/6
Mathematics
high-school
Fingolricks
asked
by
Fingolricks
5.5k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
5
votes
Answer:
y=1/3
Step-by-step explanation:
steps:
multiply each side by 6 (the fraction and y)
1. 2(3y-2)+3(2y+3)=6y+7
work problems in parentheses
2. 6y-4+6y+9=6y+7
combine like terms
3. -4+6y+9=7
4. 5+6y=7
5. 6y=7-5
6. 6y=2
7. y=2/6 =1/3
Edwina
answered
Feb 22, 2022
by
Edwina
5.8k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
1
vote
y= 1/3 see the attachment for solution
Wrokar
answered
Feb 26, 2022
by
Wrokar
5.4k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
6.0m
questions
7.8m
answers
Other Questions
Solve for y in terms of x. 2/3y - 4 = x y = x + 6 y = -x + 4 y = -x + 6 y = x + 4
Aliyah has $24 to spend on seven pencils. After buying them she had $10. How much did each pencil cost?
Ten gallons of paint were poured into two containers of different sizes. Use one variable to express the amount poured into each container
Use the normal model n(11371137,9696) for the weights of steers. a) what weight represents the 3737thth percentile? b) what weight represents the 9999thth percentile? c) what's the iqr of the weights
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org